2022
DOI: 10.21203/rs.3.rs-1674940/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes of signaling molecules in the axotomized rat facial nucleus

Abstract: Axotomy of the rat facial nerve causes downregulation of motoneuron-specific molecules, including choline acetyltransferase and the vesicular acetylcholine transporter, in surviving motoneurons. Subsequently, resident microglia are activated and proliferate. These cellular responses are thought to promote the survival, repair and regeneration of motoneurons. However, it is still unclear which signaling molecules are involved in these responses. In this study, we investigated the changes and localizations of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the facial nerve transection model using newborn rats, Graeber et al reported that the microglial cell number increased in the axotFN with a peak at 5-7 days post-injury [68]. On postnatal day 2 (p2d)-rats, the increased cell number in the axotFN reached a peak at 5-7 days post-insult [69] (Figure 2C, p2d). How does this time course compare to the case of senescent (aged) animals?…”
Section: Rat Facial Nerve Transection Modelmentioning
confidence: 91%
“…In the facial nerve transection model using newborn rats, Graeber et al reported that the microglial cell number increased in the axotFN with a peak at 5-7 days post-injury [68]. On postnatal day 2 (p2d)-rats, the increased cell number in the axotFN reached a peak at 5-7 days post-insult [69] (Figure 2C, p2d). How does this time course compare to the case of senescent (aged) animals?…”
Section: Rat Facial Nerve Transection Modelmentioning
confidence: 91%